A Simple Binary Run-Length Compression Technique for Non-Binary Sources Based on Source Mapping - Abdel-Rahman Jaradat; Mansour I. Irshid (Active and Passive Electronic Components)
In this paper, we propose a very simple and efficient binary run-length compression technique for non-binary sources. The technique is based on mapping the non-binary information source into an equivalent binary source using a new fixed-length code instead of the ASCII code. The codes are chosen such that the probability of one of the two binary symbols; say zero, at the output of the mapper is made as small as possible. Moreover, the “all ones” code is excluded from the code assignments table to ensure the presence of at least one “zero” in each of the output codewords. Compression is achieved by encoding the number of “ones” between two consecutive “zeros” using either a fixed-length code or a variable-length code. When applying this simple encoding technique to English text files, we achieve a compression of 5.44bits/character and 4.6bits/character for the fixed-length code and the variablelength (Huffman) code, respectively.